Robotic support for older adults with cognitive and mobility impairments - Olatunji, Samuel A.; Shim, James S.; Syed, Adam; Tsai, Yao-Lin; Pereira, April E.; Mahajan, Harshal P.; Mudar, Raksha A.; Rogers, Wendy A. (Frontiers in Robotics and AI, 2025)
IntroductionRobots have the potential to support older adults with cognitive impairments and mobility impairments in daily tasks that could promote their independence, enhance their abilities, ensure safety, and lower healthcare costs.MethodUsing a participatory design approach, we focused on identifying the functional capabilities of the Stretch robot to support older adults with various cognitive or mobility impairments. Twelve participants (aged 60–97) were recruited to interact with the robot and give feedback regarding support in a home environment. Stretch is a mobile robot manipulator designed to support everyday activities using a lightweight telescoping arm mounted on a mobile base. We conducted a semi-structured interview with participants as they observed and interacted with Stretch, performing tasks such as providing reminders, picking up and delivering items, and facilitating video calls.Results and DiscussionThe participants were asked to share potential areas of application related to their daily activities to illustrate how Stretch could support them in their homes. Our user-centered design approach provided a unique opportunity to understand the needs of older adults with mobility impairments and cognitive impairments, to identify the type of tasks the robot could support, and to gain insights into potential facilitators and barriers for robot adoption.